SISTEM INFORMASI INVENTORY STOK MAINTENANCE PADA PT. TOWER BERSAMA INFRASTRUCTURE, TBK BERBASIS WEB: Inventory Information System;Stock Of Goods;Maintenance;Web. - Simorangkir, Lucy; Tarmizi Taher, Muhammad (JURNAL AKADEMIKA, 2022)
Tower Bersama Infrastructure,Tbk is a company engaged in providing network tower services. Currently, the process of processing inventory stock maintenance data is still done manually, so it takes a long time and is less accurate. The purpose of this research is to build a Web-based inventory stock maintenance information system, to facilitate the data processing so that it becomes fast, precise and accurate. This information system was built using the PHP programming language and MySQL as the database. The input data needed are stock data, maintenance team data, supplier data, user data, incoming goods and outgoing goods. The process carried out is the process of incoming goods data, outgoing goods data, supplier data, and team data, while the output is in the form of stock data reports, maintenance team data reports, supplier data reports, incoming goods data reports, and outgoing goods data reports. The expected result of this research is to create a web-based inventory information system that can simplify inventory and speed up the process of delivering inventory information.